Antioxidant capacity of polychaetes occurring at a natural CO2 vent system: Results of an in situ reciprocal transplant experiment. (December 2015) - Ricevuto, E.; Benedetti, M.; Regoli, F.; Spicer, J.I.; Gambi, M.C.
Abstract: Ocean acidification (OA) is occurring at a fast rate, resulting in changes of carbonate chemistry in the oceans and in lowering of the pH. Previous studies have documented significant changes in the antioxidant defenses of marine species in response to OA. Here, selected polychaete species, Platynereis dumerilii, Polyophthalmus pictus and Syllis prolifera, were sampled from a natural CO2 vent system (pH = 7.3) and from a non-venting 'control' site (pH = 8.1), and reciprocally transplanted in these areas for 30 days. Total antioxidant capacity toward different forms of oxyradicals was compared in native and transplanted polychaetes: the aim was to assess whether the environmental conditions at the vent site would act as a prooxidant stressor, and the capability of polychaetes to modulate their antioxidant capacity to counteract a varied oxyradicals formation. None of the investigated species enhanced the antioxidant potential during the experiment. A significant reduction of the capability to neutralize different forms of oxyradicals was observed in P. pictus and, partially, in S. prolifera when transplanted from control to naturally-acidified conditions. On the other hand, populations of P. dumerilii originating from the vent and of S. prolifera from both control and acidified sites, showed higher constitutive antioxidant efficiency toward peroxyl radicals and peroxynitrite, which may allow them to cope with short-term and chronic exposure to higher oxidative pressure without further enhancement of antioxidant defenses. Since low pH – high p CO2 is the greatest environmental difference between the control and the vent sites, we suggest that the pro-oxidant challenge due to such peculiarities may have different biological consequences in different polychaete species. Some appear more susceptible to oxidative effects, while others acquire a long term acclimatization to vent conditions through the enhancement of their basal antioxidant protection. Highlights: Effects of in situ acidification were tested for polychaetes at natural CO2 vents. Reciprocally transplanted species altered their oxidative stress susceptibility. Antioxidant capacity decreased in more sensitive species at the vent site. Enhanced basal antioxidant protection is a long term adaptation strategy. Tolerance of, and resilience to, acidification in polychaetes need further studies.